Facile synthesis of doped CxNy QDs as photoluminescent matrix for direct detection of hydroquinone - Jaiswal A.; Kumar A.; Prakash R. (My University, 2025)
In this work, we are reporting facile hydrothermal synthesis of a highly photoluminescent doped carbon nitride quantum dots (CxNyQDs) and implied it for direct detection of hydroquinone (H2Q) by photoluminescence quenching phenomenon. Oxygen and sulphur moieties are regarded as dopant species in CxNyQDs and sourced from cheap solid precursors viz. cysteine and maleic acid. Morphological studies of CxNyQDs have done by SEM and TEM techniques, while structural analysis has carried out using FTIR, XPS, EDS and UV–Visible spectroscopy. The strong tendency of dispersivity of this QD in water has revealed by its zeta potential value of −32.4 mV. Optical properties of the as-prepared QDs have optimized at different excitation wavelengths. The photoluminescence stability of the dispersion is tested in various pH solutions and under continuous UV irradiation (365 nm). After that, sensing property is observed in quenching of photoluminescence feature of as-prepared QDs by direct addition of various concentrations of H2Q. We obtained lower detection limit (LOD) of 50 nM (S/N = 3) in linear range from 12 to 57.5 μM. The reduction in photoluminescence of QDs may be attributed to electron transfer from QDs to oxidized H2Q via -S− and -COO− groups present at its surface. Further, as-prepared QDs matrix exhibited high selectivity for hydroquinone over a range of potential interfering agents. Thus, the present work shows cost-effective facile synthesis of highly stable O- and S-doped carbon nitride (CxNy) quantum dots as promising photoluminescent sensor for pollutant hydroquinone without help of any enzyme or polymer assisted system. © 2020 Elsevier B.V.